Antarctic ozone depletion between 1960 and 1980 in observations and chemistry–climate model simulations - U. Langematz; F. Schmidt; M. Kunze; G. E. Bodeker; P. Braesicke (Atmospheric Chemistry and Physics, 2016)
The year 1980 has often been used as a benchmark for the return of Antarctic ozone to conditions assumed to be unaffected by emissions of ozone-depleting substances (ODSs), implying that anthropogenic ozone depletion in Antarctica started around 1980. Here, the extent of anthropogenically driven Antarctic ozone depletion prior to 1980 is examined using output from transient chemistry–climate model (CCM) simulations from 1960 to 2000 with prescribed changes of ozone-depleting substance concentrations in conjunction with observations. A regression model is used to attribute CCM modelled and observed changes in Antarctic total column ozone to halogen-driven chemistry prior to 1980. Wintertime Antarctic ozone is strongly affected by dynamical processes that vary in amplitude from year to year and from model to model. However, when the dynamical and chemical impacts on ozone are separated, all models consistently show a long-term, halogen-induced negative trend in Antarctic ozone from 1960 to 1980. The anthropogenically driven ozone loss from 1960 to 1980 ranges between 26.4 ± 3.4 and 49.8 ± 6.2 % of the total anthropogenic ozone depletion from 1960 to 2000. An even stronger ozone decline of 56.4 ± 6.8 % was estimated from ozone observations. This analysis of the observations and simulations from 17 CCMs clarifies that while the return of Antarctic ozone to 1980 values remains a valid milestone, achieving that milestone is not indicative of full recovery of the Antarctic ozone layer from the effects of ODSs.